Exactly as you are : the life and faith of Mister Rogers - Tuttle, Shea, 1983- (William B. Eerdmans Publishing Company, 2019)
"In Search of Mister Rogers pursues a rich understanding of this good, kind, sometimes strange, deeply influential, holy man: the neighborhood he came from, the neighborhood he built, and the kind of neighbor he, by his example, calls all of us to be even now, in our own troubled time"--